European Union-Russia co-operation in the field of foreign and security policy - Jović-Lazić Ana (Međunarodni Problemi, 2009)
The author examines the development of co-operation between Russia and the European Union in the field of foreign and security policy. The research reveals that despite a common interest of Russia and the EU to build a real partnership in this area based on mutual interrelatedness and interdependence, there is still a big gap between the rhetoric and cooperation in practice. The explanations can be found in different expectations and interests of what both sides are trying to achieve through this cooperation. Although EU-Russia cooperation in foreign policy and security matters is still incomplete, some formal steps towards establishing true cooperation in this field have been taken.